Freeze dried cryoprecipitate: a clinical evaluation. Issue 5 (May 1983) - Hambley, H; Davidson, J F; Walker, I D; Small, M; Prentice, C R
Abstract : Freeze dried cryoprecipitate was used in the treatment of 14 patients with haemophilia A. The in vivo recovery was 91.2% which is comparable to that reported from other parts of Europe. The product was efficacious and no adverse effects were reported. Freeze dried cryoprecipitate is the high yield product of a low technology process and as such may be of value in reducing any possible shortfall in the factor VIII requirements of the haemophiliac population of the UK.